Genetic diversity and phylogenetic reconstruction of horseshoe crabs from East Java, Indonesia based on DNA barcode COI - DWI ANGGOROWATI RAHAYU; RENI AMBARWATI; ULFI FAIZAH; ENDIK DENI NUGROHO; RUSDIANTO RUSDIANTO; PURITY SABILA AJININGRUM; NOORHIDAYAH BINTI MAMAT (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Rahayu DA, Amarwati R, Faizah U, Nugroho ED, Rusdianto, Ajiningrum PS, Mamat NB. 2024. Genetic diversity and phylogenetic reconstruction of horseshoe crabs from East Java, Indonesia based on DNA barcode COI. Biodiversitas 25: 3789-3802. Horseshoe crabs or mimi mintuna (Indonesian) are an ancient arthropod with 4 species, but there are limited studies on the species from East Java. This indicates the need for the collection of more accurate genetic resources as an important step for its conservation. Therefore, this study aims to examine genetic diversity and phylogenetic reconstruction of horseshoe crabs from East Java using DNA barcode COI. A total of 20 samples were obtained from Beejay Bakau Resort, Probolinggo, Kenjeran Beach, Surabaya, Batah Timur Beach, Madura, and Lekok Beach, Pasuruan. The 621 bp CO1 gene sequence was used for genetic diversity analysis and phylogenetic tree reconstruction. Subsequently, muscle samples were preserved in pure-grade ethanol and subjected to DNA extraction, polymerase chain reaction (PCR), sequencing, and sequence analysis. The sequence data were analyzed using bioinformatics tools, Barcode of Life Data Systems (BOLD) Systems, the Automatic Barcode Gap Discovery (ABGD) web application, and haplotype network. Phenetic taxonomy was further applied using Ntysc to enhance the robustness of the genetic analysis. The results showed that the high haplotype diversity (Hd) of 0.957, 16 haplotypes, and nucleotide diversity (?) of 0.00097 indicated a wide range of genetic variations. The frequency of parsimony informative sites was 26.48%, with 19 polymorphic sites and an overall ts/tv ratio of 2.32. In addition, the phylogenetic trees showed a clear and unambiguous branching pattern for cluster Carcinoscorpius rotundicauda Latreille 1802 and Tachypleus gigas O.F.Müller 1785. This finding is a matter of concern for managing and conserving horseshoe crab species in East Java waters.